Stop-loss - Peirce, Kimberly; Roybal, Mark.; Rudin, Scott, 1958-; Goodman, Gregory, 1959-; Richard, Mark.; Phillippe, Ryan, 1974-; Cornish, Abbie, 1982-; Tatum, Channing; Gordon-Levitt, Joseph, 1981-; Hinds, Ciaran; Olyphant, Timothy; Rasuk, Victor, 1984-; et al. (Hollywood, Calif. : Paramount Home Entertainment, 2008)
Decorated Iraq war hero Sgt. Brandon King makes a celebrated return to his small Texas hometown following his tour of duty. He tries to resume the life he left behind with the help and support of his family and his best friend, Steve Shriver, who served with him in Iraq. Along with their other war buddies, Brandon and Steve try to make peace with civilian life. Then, against Brandon's will, the Army orders him back to duty in Iraq, which upends his world. The conflict tests everything he believes in - the bond of family, the loyalty of friendship, the limits of love and the value of honor.
DVD, region 1, widescreen presentation; Dolby Digital 5.1 surround.
English, dubbed French or dubbed Spanish dialogue, English, French or Spanish subtitles; closed-captioned.
Ryan Phillippe, Abbie Cornish, Channing Tatum, Joseph Gordon-Levitt, Ciaran Hinds, Timothy Olyphant, Victor Rasuk, Rob Brown.
Director of photography, Chris Menges ; editor, Claire Simpson ; music, John Powell ; costume designer, Marlene Stewart ; production designer, David Wasco.
MPAA rating: R; for graphic violence, pervasive language, and some strong sexuality.
Special features: Commentary by director Kimberly Peirce and co-writer Mark Richard; "The making of Stop-loss" featurette; "A day in boot camp" featurette; 11 additional scenes.
Keywords: United States. -- Army -- Military life -- Drama; Soldiers -- United States -- Drama; Iraq War, 2003- -- Drama; Male friendship -- Drama; Soldados -- Estados Unidos -- Teatro; Amistad -- Estados Unidos -- Teatro; United States. -- Army -- Military life -- Drama; Soldiers -- United States -- Drama; Iraq War, 2003- -- Drama; Male friendship -- Drama; Feature films; Fiction films; War films; Video recordings for the hearing impaired; War -- Feature; Family -- Feature; Feature films; War films